2018
DOI: 10.1002/jcp.27136
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic and therapeutic values of long noncoding RNA PANDAR in colorectal cancer

Abstract: Long noncoding RNAs (lncRNAs) consist of 200 nucleotide sequences that play essential roles in different processes, including cell proliferation, and differentiation. There is evidence showing that the dysregulation of lncRNAs promoter of CDKN1A antisense DNA damage-activated RNA (PANDAR) leads to the development and progression in several cancers including colorectal cancer, via p53-dependent manner. This suggests that these lncRNAs may be of value as prognostic indices and a therapeutic target, as a high exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…18 Besides, the value of lncRNAs in cancer diagnostics, prognostics, and therapeutics has been recognized. 19,20 The ceRNA hypothesis holds that lncRNAs could serve as sponge of target miRNAs. This sets a new direction for the research on tumor diagnosis, prognosis, and targeted treatment.…”
Section: Rt-qpcr Of Candidate Lncrnasmentioning
confidence: 99%
“…18 Besides, the value of lncRNAs in cancer diagnostics, prognostics, and therapeutics has been recognized. 19,20 The ceRNA hypothesis holds that lncRNAs could serve as sponge of target miRNAs. This sets a new direction for the research on tumor diagnosis, prognosis, and targeted treatment.…”
Section: Rt-qpcr Of Candidate Lncrnasmentioning
confidence: 99%
“…LncRNA PANDAR (promoter of CDKN1A antisense DNA damage activated RNA) has been reported to be overexpressed in cancer tissues and associated with poor prognosis in many types of human cancer, including colorectal cancer,37 renal cell carcinoma,38 and bladder cancer;39 while in lung cancer the correlation of PANDAR is found to be opposite.40 In gastric cancer, PANDAR could promote the malignant progression by regulating CDKN1A gene transcription in a p53-dependent manner.11 LncRNA FOXD2-AS1 might play important roles in kinds of cancer like glioma,41 colorectal cancer.42 It has been found that upregulation of FOXD2-AS1 could promote carcinogenesis and predict poor prognosis in gastric cancer both in vitro and in vivo. Cell cycle and DNA-replication-related genes should be involved in FOXD2-AS1 function.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The study also found that high expression of PANDAR may represent a new prognostic marker for patients with CRC. Based on previous studies, the overexpression of PANDAR in CRC, breast cancer, and other tissues is related to the decrease in oxygen saturation, indicating its potential as a biomarker of poor prognosis ( Rivandi et al, 2019 ).…”
Section: General Application Of Rnaimentioning
confidence: 96%